Caregiver’s Opinions on the Design of the Screens of a Future Gamified Mobile Application for Self-Management of Type 1 Diabetes in Children in Saudi Arabia - Demah M. Alsalman; Zahra Bu Ali; Zainab Alnosaier; Norah Alotaibi; Turki M. Alanzi (International Journal of Telemedicine and Applications)
The objective of this study was to design the screens of a future gamified mobile application for self-management of type 1 diabetes in children based on the opinion of caregivers at the King Fahad Hospital Diabetes Center, Saudi Arabia. To achieve this objective, a questionnaire was designed and distributed among 100 caregivers through face-to-face communication and social media using a Google Forms link. 65% of the participants met the inclusion criteria. The main result of this study was the design of 13 screens of a gamified application for self-management of type 1 diabetes in children from Saudi Arabia. The key features of the screens were caring for a character; using a challenging friend; inclusion of points, level, and leaderboard as rewarding principles; use of reminders and notifications for doctor’s appointments, insulin injection times, blood glucose readings; and tips for improving medication adherence, increasing blood glucose readings, supporting physical activities, and adopting healthy eating habits. It can be concluded that the practical implementation of the screens in a future mobile application can motivate children with type 1 diabetes to improve eating habits, physical exercise, and cognitive, emotional, and social behaviors to maintain a stable state of health. Also, the content of the designed screens can help to monitor blood glucose readings and comply with medication treatment. The designed screens are adapted to the Arab culture.